EFEKTIVITAS VARIASI DOSIS KAPORIT DALAM MENURUNKAN KADAR AMONIAK LIMBAH CAIR RUMAH SAKIT ROEMANI MUHAMMADIYAH SEMARANG - Arivia Ulliaji; Tri Joko; Hanan Lanang Dangiran (Jurnal Kesehatan Masyarakat (Undip), 2016)
Wastewater from the hospital is one source of water pollution potential. According to preliminary test result in Roemani Muhammadiyah Semarang Hospital on 2015 obtained the result of the test parameter of average ammonia is 4,5 mg/l. Such results would exceed the quality standards according to the Peraturan Menteri Lingkungan Hidup No 5 Tahun 2014 about wastewater quality standard that is equal to 1 mg/l. The purpose of this research was to know the effectiveness of the variation dosage of calcium hipochlorite to decrease the ammonia levels of Roemani Muhammadiyah Semarang Hospital wastewater. Type this research is quasi-experiment with pre test-post test with control design. The research object is Roemani Muhammadiyah Hospital Semarang wastewater. Processing using variations of doses (650, 700, 750, 800, and 850 mg/l) chlorine in the treatment group with 5 repetitions. The statistical test used is One Way ANOVA with a confidence level of 95% and a significance level of 5% (α = 0,05). Variations chlorine dose is 650, 700, 750, 800, and 850 mg/l ammonia produces a decrease of 98,43%, 99,08%, 99,06%, 98,81% and 98,90%. The results obtained by different test p-value 0,219, showed no significant difference in effectiveness between the ammonia reduction in calcium hypochlorite dose variation. The results of this study show that the addition of calcium hypochlorite dose variation is very effective in lowering levels of ammonia Roemani Muhammadiyah Semarang Hospital wastewater.Further research is needed to use the system continuously to be applied according to the existing field conditions.